2010
DOI: 10.1634/theoncologist.2009-0298
|View full text |Cite
|
Sign up to set email alerts
|

Limited-Stage Small Cell Lung Cancer: Current Chemoradiotherapy Treatment Paradigms

Abstract: In the U.S., the prevalence of small cell lung cancer (SCLC) is declining, probably reflecting the decreasing prevalence of tobacco use. However, a significant number of patients will receive a diagnosis of SCLC, and approximately 40% of patients with SCLC will have limited-stage (LS) disease, which is potentially curable with the combination of chemotherapy and radiation therapy. The standard therapy for LS-SCLC is concurrent chemoradiotherapy, and the 5-year survival rate observed in clinical trials is appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 69 publications
1
50
1
3
Order By: Relevance
“…In the beginning, chest irradiation in SCLC was broad and covered the entire mediastinum. Currently, with further technical progresses, radiation field is limited and toxicity decreased (26). A phase III study performed in 471 patients with limited SCLC (27) showed that 5-year survival increased with radiotherapy given twice-daily (1.5 Gy, 30 fractions) compared with once-daily (1.8 Gy daily in 25 fractions) (P=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning, chest irradiation in SCLC was broad and covered the entire mediastinum. Currently, with further technical progresses, radiation field is limited and toxicity decreased (26). A phase III study performed in 471 patients with limited SCLC (27) showed that 5-year survival increased with radiotherapy given twice-daily (1.5 Gy, 30 fractions) compared with once-daily (1.8 Gy daily in 25 fractions) (P=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Survival benefit that radiotherapy intervention was carried out on the first day or 22 days of chemotherapy (early radiotherapy) in patients was superior to that of radiotherapy intervention was implemented on the first 36 days or 106 days of chemotherapy (late radiotherapy): median survival time was respectively 21.2 months vs.16 months (p=0.008) and 34 months vs 26 months (p=0.052) (Murray et al, 2003;Jeremic et al, 2007). However, unfortunately, the other Phase III clinical studies did not obtain the consistent results (Stinchcombe et al, 2010). Currently, the results of phase III clinical studies are not all transformed to operational guidelines, then whether the Meta-analysis based on above data can provide some valuable information?…”
Section: Discussionmentioning
confidence: 98%
“…2 important meta analysis had confirmed that chest radiotherapy can not only reduce the local recurrence rate, but also can improve the survival rate of the patients. Therefore, systemic chemotherapy and local accelerated hyperfractionated thoracic radiotherapy had became the standard treatment for small cell lung cancer for it could significantly improve local control rate, prolong the survival time of patients, and patients could well tolerate the treatment side effects (Stinchcombe et al, 2010;Kalemkerian et al, 2011;Amini et al, 2014). Prophylactic cranial irradiation (PCI) is recommended for patients achieving a complete response (CR) due toNowadays, the golden treatment for LD-SCLC is concurrent chemoradiotherapy, but the precise intervention time of radiotherapy is still inconclusive (Manapov et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the timing of radiation therapy continues to be debated, the 2011 NCCN guidelines in SCLC state that there is category 1 evidence to support concurrent chemoradiotherapy over sequential therapy for fit patients (Stinchcombe and Gore, 2010;Komatsu et al, 2011;NCCN, 2011).…”
Section: Modalities and Timing Of Radiotherapymentioning
confidence: 99%